Development of a Clinical Nursing Practice Guideline for Prevention of Unplanned Extubation in Medical Intensive Care Unit, Mahasarakham Hospital: Nalinrat Promso - Promso, Nalinrat; Wongpiriyayothar, Apinya; Buatee, Supatra (Princess of Naradhiwas University Journal, 2024)
The purpose of this study was to develop a clinical nursing practice guideline based on advanced nurse practitioners’ evidence-based practice to minimize unplanned extubation. There were three phases involved: phase one involved investigating clinical problems, phase two involved finding practice-relevant information, and phase three involved testing a clinical nursing practice guideline. A quasi-experimental study was conducted. Samples of this study were twelve nurses and sixty-two patients, split into control and experiment groups. In each group, there were thirty-one patients. The instruments utilized in the data collection process were the unplanned extubation incidence record form and the feasibility of a clinical nursing practice guideline form. The statistics used in this study were descriptive statistics and Chi-square test. The results found that there were four components of a clinical nurse practice guideline for prevention of unplanned extubation: risk assessment for unplanned extubation; 2) nursing care during intubation; 3) information regarding intubation and communication; and 4) management administration. The results found that there were 8.47 and 4.44 unplanned extubation incidents in the control group and experimental group, respectively, throughout 1000 days of intubation. The proportion of unplanned extubations did not statistically substantially different between the two groups (χ 2 = .350, p > .05). Nurses exhibited a 100% of a high level in feasibility rate for applying the practice guideline. The usage of this nursing practice guideline was deemed feasible. There was no discernible difference between unplanned extubation and short term usage. As a result, nurses ought to follow nursing practice guidelines for a longer period of time.